Health and social burden of alcohol use disorders in an industrial population of India - Ray, Gautam (International Journal Of Community Medicine And Public Health, 2023)
Background: In the last two decades the rate of alcohol consumption has substantially increased in India but the socioeconomic burden of alcohol use disorders (AUD) is understudied. Methods: 48613 patients admitted from January 2009 to December 2018 for diseases directly or indirectly related to alcohol use (40.1% of total admission) were analysed. Retrospective analysis of prospectively maintained data was used as current study design. Diagnosis were arrived at by history, clinical examination and relevant investigations. Social data included demography, alcohol related information, social, emotional, psychological aspects and occupation related issues. Results: There was a rising trend of both direct (59.3%) and indirect (40.7%) alcohol related disorders over the years with the following rates: injuries (30.6%), gastrointestinal disorders (16.7%), AUD (6.2%), other substance abuse (4.1%), seizures (1.7%), infections (16.7%), only diabetes mellitus (1.9%), gastrointestinal cancer (4%), cardiovascular disease (4.3%), neurovascular disease (8%) and chronic kidney disease (5.8%). 39.7% patients had pulmonary tuberculosis. This entailed a yearly hospital expenditure of INR 165.54 million and an additional INR 10.3 million for work absenteeism. 37.6% died whereas disability and poor work productivity led to relocation and premature retirement in 7.2%. Social aspects revealed early initiation of drinking (73% at <30 years of age) at instances of family/ friend in a conducive setting of easy availability and permissive “drinking environment” furthered by vissisitudes in later life. Heavy consumption of spirits (average 118 gm/day), often in binges, fortends serious health consequences. Conclusions: Alcohol related socioeconomic burden is rapidly rising in India and needs urgent attention.